An Interview with a Goddess: Possession Rites as Regulators of Justice Among the Pnar of Northeastern India - Lyngdoh, Margaret (Religious Studies and Theology, 2017)
This article is based on primary fieldwork carried out between 2012 and 2017 in Chyrmang, Jaintia Hills. Among the Pnar of Jaintia Hills, Northeastern India, the practice of hiar blai or divine possession is significantly embedded in the everyday lives of the community members. I argue that possession rites mediate and regulate social norm and clan justice, through the intercession of the gods and goddesses in the village. The reflexive nature of fieldwork process sought to demonstrate the non-absolute positionality of the researcher, and informants and attempted to find ways how to articulate informant’s voices while at the same time protecting their identities.